Effect of inoculum size on Haemophilus influenzae type b susceptibility to new and conventional antibiotics. - Laferriere, C (1983)
Thirty-three Haemophilus influenzae type b isolates, including beta-lactamase acetyltransferase-positive strains, were tested by microtiter broth dilution for susceptibility to eight beta-lactam compounds and chloramphenicol. All antibiotics except ampicillin and chloramphenicol were highly bactericidal against all isolates at an inoculum of 10(5) CFU/ml. However, at an inoculum of 10(5) CFU/ml, the minimal bactericidal concentrations of all drugs except ceftriaxone were above levels usually achievable in cerebrospinal fluid. Results of time-kill studies confirmed this inoculum effect. In vivo studies are needed to test the clinical impact of these observations.